Okun’s Law at the Florida MSA Level - Stinespring, Johnert Robert; Luciene, Jeremy Adam (Journal of Applied Business and Economics, 2019)
This paper applies a fixed effects panel data spatial econometric model of Okun’s law to Florida Metropolitan Statistical Areas (MSAs) over the period 1990 to 2015. The regression coefficients are used to estimate the impact of increases in output on unemployment and each MSA’s potential rate of output growth. Results indicate that Okun’s coefficient ranges from -0.19 to -0.24 at the MSA level. Between one-half to two-thirds of changes in local unemployment occur as a spillover effect from neighboring MSA output growth. Each MSA’s potential real output growth rate averages between 1.7 to 2.7 percent.